2015
DOI: 10.1039/c5ra00427f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning N-methyl-d-glucamine density in a new radiation grafted poly(vinyl benzyl chloride)/nylon-6 fibrous boron-selective adsorbent using the response surface method

Abstract: A new adsorbent containing boron-selective groups was prepared by radiation induced grafting of vinyl benzyl chloride (VBC) onto nylon-6 fibers followed by functionalisation with N-methyl-D-glucamine (NMDG). The density of glucamine loaded in the adsorbent was tuned by optimisation of the reaction parameters such as NMDG concentration, reaction temperature, reaction time and degree of grafting using response surface methodology (RSM) employing Box-Behnken design (BBD). The optimum parameters for achieving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…In the second modification step, NMDG was appended to the pore walls of the frameworks via a nucleophilic substitution reaction with the –CH 2 Cl groups. Successful incorporation of NMDG was confirmed via FTIR spectroscopy, with the disappearance of the band at 1266 cm −1 and the appearance of three new bands at 1072, 1017, and 3300–3600 (broad) cm −1 that were attributed to the C–O, C–N, and hydroxyl groups of NMDG, respectively . Further support for successful incorporation of NMDG was afforded from MAS 13 C NMR spectroscopy, with the appearance of a broad resonance at ≈72 ppm that was attributed to the carbon atoms in NMDG.…”
Section: Pseudo‐second‐order Rate Model Parameters For Experiments Pementioning
confidence: 83%
“…In the second modification step, NMDG was appended to the pore walls of the frameworks via a nucleophilic substitution reaction with the –CH 2 Cl groups. Successful incorporation of NMDG was confirmed via FTIR spectroscopy, with the disappearance of the band at 1266 cm −1 and the appearance of three new bands at 1072, 1017, and 3300–3600 (broad) cm −1 that were attributed to the C–O, C–N, and hydroxyl groups of NMDG, respectively . Further support for successful incorporation of NMDG was afforded from MAS 13 C NMR spectroscopy, with the appearance of a broad resonance at ≈72 ppm that was attributed to the carbon atoms in NMDG.…”
Section: Pseudo‐second‐order Rate Model Parameters For Experiments Pementioning
confidence: 83%
“…Xu et al reported a silica-supported NMDG adsorbent (Si-MG) constructed by anchoring NMDG-modified (3glycidoxypropyl) trimethoxysilane to a silica surface with a maximum adsorption capacity of 1.54 mmol g −1 [57. Ting et al prepared a novel boron-selective adsorbent by radiation-induced grafting of vinyl benzyl chloride onto nylon-6 fibers followed by functionalization with NMDG [58]. A spherical organic-inorganic hybrid boron-selective adsorbent with organosiloxane functionalized with NMDG functional groups was also reported [59].…”
Section: Chelating Resinsmentioning
confidence: 99%
“…PE melting is reflected by a broad peak with two maxima at 105°C and 120°C, while nylon melting is associated with a narrow peak with one maximum at 219°C. DSC analysis performed separately for the nylon nonwoven (PA) has revealed that the endothermic transition characterized by a broad peak with a maximum at approximately 60°C in the first heating cycle is associated with the T g of nylon, which is obscured by a peak attributable to moisture or other substances that may be present in the commercially available product [17]. In turn, the endothermic peak above 200°C reflects crystalline phase melting in the nylon nonwoven.…”
Section: Analysis Of Thermal and Thermomechanical Propertiesmentioning
confidence: 99%